Pengaruh Digital Marketing dan Kualitas Produk Terhadap Minat Beli Pada Produk Cochic di Shopee - Perdana, Cipta Tahta; Widyastuti, Trie Andari Ratna (JAMBIS : Jurnal Administrasi Bisnis, 2025)
In today's modern era, the internet is almost the same as a primary need, easy internet access encourages changes in people's buying and selling patterns. Selling online is one of the significant changes among Indonesian people. The development of online marketplaces is also very rapid in Indonesia, starting from Lazada, Tokopedia, Shopee, and many more. This digital marketing method is then utilized by Chocic product owners to market and socialize the quality of the products they produce through the Shopee online marketplace platform, as well as to increase a wider market share. However, there are still obstacles faced by the Indonesian people in facing the massive invasion of technology in this digital era. This can be seen from some people who continue to sell via offline platform even though they know that selling online is easier and has minimal marketing costs. This research aims to analyze how much the impact of digital marketing and product quality have on purchase interest of Chocic products through the online media Marketplace Shopee. This research used a descriptive quantitative method. The data collection method used a questionnaire. The population of this research was internet users who had shopped online and had used Shopee so that the number was incalculable. Sampling used the Heir formula of 145 people with non probability sampling and accidental sampling techniques. The data analysis technique used multiple linear regression and used the SPSS 26 application. Digital marketing (X1) has a significant effect on purchase decisions (Y) of Chocic products on Shopee by 65.2%. Product quality (X2) has a significant effect on purchase decisions (Y) of Chocic products on Shopee by 63.4%. The results of the F test of the variables digital marketing (X1) and product quality (X2) simultaneously were 69.6%, while 30.4% was influenced by other factors that were not known and not included in the regression of this research.